AN AUTHENTIC ASSESSMENT ON SENTENCE COMPLEXITY TOWARD INDONESIAN EFL STUDENTâS WRITING PRODUCTION - Mahendra, Made Wahyu (Pusat Pengembangan Bahasa, 2016)
Linguistically, the more complex clause a sentence implements, themore complex the grammar it embed. A simple clause, as opposingthe complex clause, consists of a subject and a verb with optionalobject or complement. However, Biber et.al. (2011) has provedthat complexity of a clause attached in a sentence fails to indicatethe complexity of a sentence in writing composition. Furthermore,they indicated the stage of the acquisition of complexity features ofwriting, including that of in L2 of English. This present study aimsat investigating how the frequency of complex sentence produced byGanesha University of Education students different from that of byprofessional academic writer, to assess studentsâ writing ability. Thecomplexity features of writing comprise: 1) fnite dependent clausetypes; 2) non-fnite dependent clause; and 3) dependent phrase types(non-clausal). Theoretically, the implication of the study aims to beneftthe development of teaching writing through authentic assessmentprocess. Providing assessment with diagnostic feedback on areasof needed improvement through authentic assessment in Englishlanguage teaching has become a solution due to its signifcance forlanguage learner (Brown & Abeyvikrama, 2010: 254). Corpus-basedanalysis is conducted allowing great number of data to be analyzed togenerate more reliable generalization (Baker, 2010). The corpus dataand the frequency of sentence complexity as represented by selectedfeatures of (Biber et al., 2011), are annotated using CLAWS part-of-Made Wahyu Mahendra, An Authentic Assessment....46.speech tagger hosted by Ucrel, and are calculated by Ant.Conc 3.2.4corpus software. The fndings projects surprisingly occurrence inwhich undergraduate students utilizes clausal sentence rather thanphrasal sentences. It becomes indication that the students are in theearly developmental stage of complexity in writing.